Efektifitas Ekstrak Daun Beluntas (Pluchea indica L) Terhadap Kualitas Karkas Ayam Broiler - Julinda Romauli Manullang; Arie Saputra; Servis Simanjuntak (Fakultas Pertanian Universitas Majalengka, 2024)
The effect of adding beluntas leaves to drinking water on feed consumption, feed utilization, live weight gain and mortality in broiler chickens. Research using the Completely Randomized Design (CRD) method with 5 treatments and 5 replications. P0 without treatment, then the addition of beluntas leaf extract P1 = 4%, P2 = 6%, P3 = 8%, and P4 = 10%. Research data were analyzed using analysis of variance (ANOVA), if there is a significant difference followed by DMRT test at 5% level. The results showed that the provision of beluntas leaves had no significant effect on body weight, carcass percentage and abdominal fat (ANOVA).